Enhancing online rapport experience via augmented reality. Issue 7 (13th November 2019) - Huang, Tseng-Lung; Mathews, Shane; Chou, Cindy Yunhsin
Abstract : Purpose: The purpose of this study is to draws on self-determination and self-evaluation theories to examine the psychological factors impacted by augmented reality (AR) services, an augmented reality try-on system. This study highlights three characteristics of modality, synchronous sense or ownership and re-processability within an AR try-on experiences as well as the moderating effects of consumers' body surveillance and fashion consciousness. Design/methodology/approach: Using a scenario survey approach, this study designs characteristics of an AR try-on system to examine the research model and the hypotheses. A total of 207 responses are collected and analysed using the SmartPLS 3 statistical software. Findings: The results show that modality, synchronous sense of ownership control and re-processability of AR try-on system positively affect consumer's rapport experience. Both body surveillance and fashion consciousness significantly moderate the effects of AR try-on service system characteristics on consumer rapport experience. Research limitations/implications: This study highlights the importance of understanding the implications of the evolution of cyborg consumerism where consumer technology interface systems such as AR, as a source of technologically mediated modality, become part of the consumer's body, an extension of their body if you will. Practical implications: Based on the study findings, marketing managers can understand how to better use AR to implement digital promotional strategies for various body-involvement products. Originality/value: Using immersive technologies, this study shows that AR allows a consumer see an authentic self and tangible extension of their physical self in an online shopping setting, thus enhancing a consumer's online shopping experience.